Respuesta :

Answer:

[tex]\frac{2}{3}+(-2\frac{1}{3})=-1 \frac{2}{3}[/tex] is correct.

Step-by-step explanation:

The number line between two consecutive integers is divided into 3 intervals. This means each of these intervals is 1/3. For example, starting from 0 towards right the first small line is at 1/3, the next at 2/3 and then at 3/3 = 1.

Similarly, towards the left of 0, we have -1/3, -2/3 and then-1. Based on this data, we can find the end points of the given line

  • The location of right end point is 2/3
  • The location of left end point is [tex](-1\frac{2}{3} )[/tex]

The distance between two endpoints can be calculated as:

Right End point - Left End point

[tex]=\frac{2}{3} - (-1\frac{2}{3})\\\\ =\frac{2}{3} + 1\frac{2}{3}\\\\ =\frac{2}{3}+\frac{5}{3}\\\\ =\frac{7}{3}\\\\ =2\frac{1}{3}[/tex]

So, the equation can be set up as:

[tex]\frac{1}{3}-(-1\frac{2}{3})=2\frac{1}{3}\\\\ \frac{1}{3}= 2\frac{1}{3}+(-1\frac{2}{3})\\\\ \frac{1}{3}-2\frac{1}{3}=-1\frac{2}{3}\\\\ \frac{1}{3}+(-2\frac{1}{3})=-1\frac{2}{3}[/tex]

Which matches with the final option.

Keywords: addition, graph, number line

Learn more addition and number line from brainly.com/question/5057056

#learnwithBrainly

Answer:

The answer is 2nd equation

Step-by-step explanation:

Since, this line goes from [tex]\frac{2}{3}[/tex] till [tex]-1-\frac{1}{3}[/tex], therefore,

[tex]\frac{2}{3} + (-1-\frac{1}{3})[/tex]

[tex]\frac{2}{3} + (-\frac{4}{3})[/tex]

[tex]\frac{-2}{3}[/tex]

[tex]-1\frac{1}{3}[/tex]

and this is equal to right hand side of the equation in option two, i.e.

[tex]\frac{2}{3} + (-2) = -1\frac{1}{3}[/tex]

Hence, 2nd equation is the answer.